Social Shopping Relationship Management on Social E-Commerce in Indonesia (Case Study: Online Food Consumers) - Nugraha, Marza Riyandika; Sumarwan, Ujang; Yulianti, Lilik Noor (UI Scholars Hub, 2021)
Abstract: The phenomenon of online shopping and business start-ups are rising in Indonesia, and one of the results of this movement is a new form of e-commerce—social shopping—which combines two online activities: social networking and online shopping. Manuscript type: Case Studies Research Aims: The purpose of this paper is to improve academic understanding on social shopping websites and to research the impact of relationship quality and the ensuing effect on individuals’ online loyalty to social shopping websites. Design/methodology/approach: This paper examines factors that may affect consumer behaviour in social shopping websites. This study proposes a conceptual framework which uses Google forms to gather information from members who have made at least one previous online food purchase. Data was collected from Kaskus.com, a social shopping website in Indonesia. The authors analyzed the model using the structural equation modelling approach. Research Findings: The results show that members’ perceived social network, message source credibility, website stimuli, and argument quality are important factors that affect consumer e-loyalty. In addition, both consumer website value and relationship quality strengthened this loyalty. Theoretical Contribution/Originality: This study provides a comprehensive framework to better understand the influences on the development of relationship quality and the impact on member loyalty by addressing the role of information and content creation in the social shopping environment, especially on online food consumer behaviour. Practitioner/Policy Implication: Websites should provide trusted information, attention to stimulus, facilitate user interactions, and strengthen the value of the community to increase the user’s shopping experience. Research limitation/Implications: In this research, we were limited to one product category: food, and there are other factors that should be research such as cultural factors, lifestyle, level of technology adoption, and tradition to better understand the intentions of customer loyalty.